2017
DOI: 10.1186/s12881-017-0460-1
|View full text |Cite
|
Sign up to set email alerts
|

SCN8A mutations in Chinese patients with early onset epileptic encephalopathy and benign infantile seizures

Abstract: Background SCN8A mutations have recently been associated with epilepsy and neurodevelopmental disorders. This study aimed to broaden the phenotypic-spectrum of disease related with SCN8A mutations.MethodsTo identify the pathogenic gene of a Chinese family, in which six members suffered from epilepsy, whole-exome sequencing was performed. In addition, target next-generation sequencing (NGS) was performed on 178 sporadic patients, who had epilepsy of unknown etiology within 6 months after birth. A detailed clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Only one of them died of definite SUDEP, at the age of 15 years . Two additional young patients (17 and 19 years old) had a possible/probable SUDEP, and two children (26 months and 5 years old) died after prolonged seizures, suggesting a possible SUDEP . In total, five of 235 (2.1%) patients with pathogenic SCN8A mutations died of definite or possible SUDEP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one of them died of definite SUDEP, at the age of 15 years . Two additional young patients (17 and 19 years old) had a possible/probable SUDEP, and two children (26 months and 5 years old) died after prolonged seizures, suggesting a possible SUDEP . In total, five of 235 (2.1%) patients with pathogenic SCN8A mutations died of definite or possible SUDEP.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the same variant was also found in a Chinese family with a similar phenotype . A second pathogenic variant, Asn1877Ser, has been reported both in BFIS and in sporadic cases with drug‐responsive focal epilepsy (Tables and a) …”
Section: Resultsmentioning
confidence: 99%
“…Targeting persistent sodium current, one of the common primary biophysical defects in this disorder, may provide an effective precision therapeutic approach. Reports have described patients achieving seizure control with carbamazepine, oxcarbazepine, valproic acid, and most notably, high‐dose phenytoin . Phenytoin is a state‐dependent sodium channel blocker with a small preference (~10%) for persistent current over peak current .…”
Section: Introductionmentioning
confidence: 99%
“…Reports have described patients achieving seizure control with carbamazepine, oxcarbazepine, valproic acid, and most notably, high-dose phenytoin. [11][12][13][14][15][16] Phenytoin is a state-dependent sodium channel blocker with a small preference (~10%) for persistent current over peak current. 17 However, high-dose phenytoin has significant safety concerns due to saturable metabolism and risk for phenytoin poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…This disease mechanism is reflected by the therapeutic response of VGSC blockers. Various clinical reports have shown that SCN8A-related epilepsy patients benefit from VGSC blockers [9] [10] , contrasting their inefficacy, or even detrimental effects in DS [11] . These observations indicate that Na V 1.1 and Na V 1.6 represent two opposing sides of the neuronal balance between inhibition and activation.…”
Section: Introductionmentioning
confidence: 99%